Reinforcement of the MCFC matrix by Al-based additives: Effect of lithiation. Issue 6 (15th March 2022) - Gürbüz, E.; Hubert, S.; Jordan, L.; Albin, V.; Ringuedé, A.; Lair, V.; Cassir, M.
Abstract: The matrix material in a Molten Carbonate Fuel Cell, usually LiAlO2, has an important role in the ionic conduction, gas sealing and electrolyte retention. To avoid cracking, this material has been reinforced with various additives, mostly Al-based, which are subject to in situ lithiation. In this work, matrices were systematically synthesized through a fast and more environmentally friendly route and characterized, with two types of reinforcing agent, either Al powder or Al2 O3 fibers, both with and without carbonates. Then, a comparative analysis was done, in terms of mechanical strength and porosity, on the effect of adding Al powder and Al2 O3 fibers and their subsequent lithiation. This reaction was found to be quantitative after 50 h at 650 °C, and matrices with reinforcing agent and carbonates featured increased mechanical strength by a factor up to 2 compared to matrices with only reinforcing agent, reaching 0.61 kgf.mm −2 . Al powder was also found to be better suited than Al2 O3 fibers for addition in a matrix, also contributing to enhance the porosity, particularly after lithiation.